Small-Scale Farmers' Perception of the Adoption of Agroforestry Practices in Tolon District, Ghana - Sordji Larweh; Ammal Abukari (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted in the Tolon district of Ghana to determine small-scale farmers' perceptions, motivation and problems faced by them in the adoption of agroforestry practices. Primary data were collected through a pre-structured questionnaire from a sample of 200 respondents who were selected using a multi-stage random sampling technique. Data analysis was done by using the percentage and total weighted score (TWS) method. Most of the farmers in the study area have a positive perception of the adoption of agroforestry practices. Crop diversification, high returns and risk minimisation were the major motivational factor, whereas small landholding size, lack of awareness and poor knowledge, poor market accessibility, lack of subsidy, credit facility, lack of good quality planting material and longer period for tree growth were the major problems faced by the farmers in the study area. Thus, the study suggested that farmers can be encouraged to practice agroforestry through improved agroforestry extension services, cooperative groups and distribution of quality planting material to farmers.